2023
DOI: 10.1080/02670836.2022.2157529
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Er addition and cooling rate on the corrosion resistance of Zn-5Al alloys

Abstract: Galfan (Zn-5Al-RE) coating is widely used in high-strength steel wires. The effects of cooling rate and the adulteration of erbium (Er) on the microstructure and corrosion resistance of Zn-5Al alloys were investigated in this study. The results show that the Zn-5Al alloy is made up of the primary η-Zn phase and eutectic structure at a high cooling rate. As the cooling rate decreases, the corrosion current firstly increased and then decreased due to decrease of the primary η-Zn content, the appearance and grew … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Zn-5Al is composed entirely of a coarse eutectic structure [24]. When the total content of Al is 15 wt.%, the alloy consists of both eutectoid (α+η) and eutectic (η+β) structures [25][26][27][28][29]. Furthermore, Zn-15Al can be found to have the finest eutectoid structures compared to the other three alloys [30].…”
Section: Microstructure Of As-cast Alloysmentioning
confidence: 97%
“…Zn-5Al is composed entirely of a coarse eutectic structure [24]. When the total content of Al is 15 wt.%, the alloy consists of both eutectoid (α+η) and eutectic (η+β) structures [25][26][27][28][29]. Furthermore, Zn-15Al can be found to have the finest eutectoid structures compared to the other three alloys [30].…”
Section: Microstructure Of As-cast Alloysmentioning
confidence: 97%
“…The integration of RE and Si elements into the ZAM alloy can enhance the homogeneity of the coating surface structure and stabilize corrosion products. [20] Moreover, Ge et al [21] observed that Er addition to Zn-5Al alloy generated Er-containing intermetallic compounds within the coating, refining the primary η-Zn and α-Al phases and substantially increasing corrosion resistance by densifying the corrosion products. Research indicates that the precipitated phase is enriched at the grain boundary when 0.02wt%B is added, and the electrical conductivity and mechanical properties of Al-Mg-Si alloy are significantly improved.…”
mentioning
confidence: 99%